Peran Nilai Pancasila dalam Memupuk Persaudaraan dan Toleransi Mahasiswa Prodi Teknik Industri di Universitas PGRI Adi Buana Surabaya - Cahyani Khoriq Azhari; Aditya Rafie Lutfir Rahman; Sofia Sofia; Eisya Qurrotta Akyun; Laksana Damar; Deby Oktavia; Suta Wijaya; Gian Dwi Hermawan; Ahmad Bahrul; Aditya Firmansyah; Galang Trian; Yovi Savitri; Suyono Suyono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to find out the role, implementation, and factors that affect the implementation of Pancasila values for students. This study uses a descriptive method to describe various conditions in real live in the study. The data collection technique used in this study is based on interviews that are arranged logically, systematically, and objectively to explain the variables that are collected. The results of this study show that most students of the Industrial Engineering study program at University of PGRI Adi Buana Surabaya have a good attitude of tolerance in respecting cultural, ethnic, and religious differences. Their tolerance level averages 8,5 on a scale of 1-10. This shows that the implementation of Pancasila values on campus is quite good. However, there are still a small number of students who have an attitude of intolerance. This research recommends a broader and intensive application of Pancasila values and increases student awareness regarding the importance of tolerance in society.